2007
DOI: 10.1161/strokeaha.106.479576
|View full text |Cite
|
Sign up to set email alerts
|

A New Endoluminal, Flow-Disrupting Device for Treatment of Saccular Aneurysms

Abstract: Background and Purpose-We report a preclinical study of a new endoluminal device for aneurysm occlusion to test the hypothesis that the device, even without use of intrasaccular coil placement, could occlude saccular aneurysms without causing substantial parent artery compromise or compromise of adjacent, small branch arteries. Methods-The Pipeline Neuroendovascular Device (Pipeline NED; Chestnut Medical Technologies, Inc) is a braided, tubular, bimetallic endoluminal implant aimed at occlusion of saccular ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
280
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 412 publications
(302 citation statements)
references
References 8 publications
8
280
1
1
Order By: Relevance
“…Currently, stents are used to maintain coils inside the aneurysm. It is thought that stents alone would be able to treat such disease by acting more as a "flow diverter" rather than as a "mechanical support for coils" [8,9]. Indeed, stents may aspire at three potential purposes: the aneurysmal/arterial circulation disconnection, the aneurysmal in-jet redirection, and the establishment of a scaffold useful for vessel repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, stents are used to maintain coils inside the aneurysm. It is thought that stents alone would be able to treat such disease by acting more as a "flow diverter" rather than as a "mechanical support for coils" [8,9]. Indeed, stents may aspire at three potential purposes: the aneurysmal/arterial circulation disconnection, the aneurysmal in-jet redirection, and the establishment of a scaffold useful for vessel repair.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also reported a stent-in-stent technique to increase the lateral hemodynamic resistance of the stent in dissecting or small wide-necked aneurysms [4][5][6][7]. New generation of intracranial stents and recent devices called flow diverters are thought to progressively become the current optimal minimally invasive treatment for intracranial aneurysms [8,9]. Such devices have a lower porosity and are used for stand-alone treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These are presumably associated with hemodynamic and not embolic factors. Recent studies, both in animals 11,12 and in clinical practice, 19 suggest that in the case of laminar flow, due to a high pressure gradient in the covered side branch, the side branch remains patent, even with multiple overlapping devices. 8 Thus, in cases in which an important collateral network exists or develops, a "competition" of flow may have as a result a decrease in pressure gradient between the covered ostium and the distal portion of the arterial branch, contributing in such a way to a hemodynamic "stagnation.…”
Section: Supplementary Comparison With the Department's Series Of Stementioning
confidence: 99%
“…This topic has been widely discussed in the flow-diversion literature, with the consensus suggesting that branch occlusions are not uncommon but are often clinically silent. 5,11,12 It remains unclear whether small-diameter flow diverters have a greater propensity to cause occlusion or symptomatic flow reduction to covered arterial branches, but the series by Yavuz et al 4 showed relatively high rates of branch occlusion (3/21, 14%) and a reduced caliber of the covered branch (6/21, 29%) among 21 MCA bifurcation aneurysms treated. 12 Our series demonstrated 1 case (8%) of a jailed branch artery occlusion (frontopolar artery) with an associated area of diffusion restriction on MR imaging (postprocedure day 1) suggestive of infarct, but this was clinically silent.…”
Section: -10mentioning
confidence: 99%